Structure and ultrastructure of the ventral prostate of isogenic mice (C57B1/6J) submitted to chronic alcohol ingestion - Cagnon, VHA; Tomazini, F. M.; Garcia, P. J.; Martinez, F. E.; Martinez, M.; Padovani, C. R. (Churchill Livingstone, 2001)
Morphological and functional alterations caused by chronic alcohol ingestion in testes and accessory sex organs have been studied both in man and in laboratory animals. The aim of the present study was to examine the possible occurrence of deleterious effects of chronic alcohol ingestion on the secretory epithelium of the ventral prostate of mice. Twenty-four adult male C57BL/6J mice were divided into three groups. The alcohol-treated group was allowed to drink only 6% (v/v) ethanol, the isocaloric group received a diet of water/sucrose with a calorie content equivalent to a 6% alcohol solution and the control group received water. Both groups were fed ad libitum with solid Purina rat chow. After 120 days, animals from each group were anesthetized with ethyl ether, weighed and processed for light and transmission electron microscopy. The results demonstrated reduction in the glandular epithelium cell height and disorganization of the Golgi complex. Moreover, abundant membrane-bound structures, most likely representing cytoplasmic material, were observed, as well as accumulation of dense bodies. Statistical analysis showed that bodyweight gain was similar for both groups. In conclusion, chronic alcohol ingestion has harmful effects on the secretory epithelium cells of the ventral lobe of the prostate of mice after 120 days of treatment. (C) 2001 Harcourt Publishers Ltd.
Keywords: alcohol; ultrastructure; prostate